Study of nitrogen status in different planting systems and organic fertilizer doses in sandy soil - Soeparjono, Sigit; Bintoro, Jatmiko Hardi; Khozin, Mohammad Nur; Putri, Widya Kristiyanti; Restanto, Didik Pudji (Brawijaya University, 2024)
This study was conducted to determine the effect of different jajar legowo planting systems in intercropping sweet corn with peanuts, as well as the addition of several doses of organic fertilizer on soil nitrogen status and plant leaf tissue on sandy soil. The research was conducted from January to May 2023, on the south coast of Jember Regency. The study used a split-plot design; the main plot consisted of the treatment of 2:2 (A1) and 4:2 (A2) jajar legowo intercropping systems. The subplots were different doses of cow dung organic fertilizer: 10 t ha-1 (B1), 20 t ha-1 (B2), and 30 t ha-1 (B3), each repeated three times. Observational data were analyzed by ANOVA and DMRT 5%. The results of the study showed that the combination of the planting system and organic fertilizer doses applied had not been able to provide optimal microclimate and soil properties for the growth and development of sweet corn plants. The A2 planting system provides a better microclimate and plant morphology for plant N availability and absorption. The addition of organic fertilizer up to the highest dose (B3) has not been able to maintain optimal soil water and N availability for sweet corn in sandy soil.